2014
DOI: 10.1080/14615517.2014.896082
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impact assessment of municipal solid waste disposal site in Tabriz, Iran using rapid impact assessment matrix

Abstract: The irregular and non-normative development of cities and also weakness in the waste management system has created many problems especially in large cities. However, even many of the principles of engineering and environmental criteria about burying of wastes do not match in the landfill sites. Therefore, environmental impact assessment (EIA) for landfills to examine the effects of landfills on environment is essential. Rapid impact assessment matrix (RIAM) is one of the ways that it can be used to EIA. This m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…The original ES values obtained by Taheri et al (2014) are shown in Table 2. Table 2 also includes the relative ES values obtained, as part of the model application to the RIAM results (Fig.…”
Section: Overview Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The original ES values obtained by Taheri et al (2014) are shown in Table 2. Table 2 also includes the relative ES values obtained, as part of the model application to the RIAM results (Fig.…”
Section: Overview Of Resultsmentioning
confidence: 99%
“…This paper has applied a revised mathematical model to the original RIAM results of Taheri et al (2014). This was conducted in order to determine the potential sustainability or unsustainability of four unmitigated options at the Tabriz MSW disposal site in Iran.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, composting can have a better costbenefit ratio in addition to moderate environmental impacts (Aye and Widjaya, 2006). In addition, Taheri et al (2014) recommend composting together with landfill management. Of note, some are of low quality and require an efficient municipal program with proper separation and better use of technology to purify waste (Barreira et al, 2008).…”
Section: Resultsmentioning
confidence: 99%